Some Blood Parameters in Sea Bass (Dicentrarchus labrax L) Wıth Respect to Water Quality Parameters - Hijran Yavuzcan (Journal of Agricultural Sciences)
ThiS study was conducted to determine the seasonal values of some b]ood parameters (hernat':" hemoglobin, the numbers of erythrocyte, leucocyte and trombocyte as we|l as Wintrobe erythrocyte indices) in c]lı :, healthy sea bass reared at a commercial farm, Bodrum (Turı